(untitled) (Physical Education, Health and Social Sciences, 2024)
This analysis is a theoretical examination of the geopolitical importance of the Balochistan province which presents the province as a significant geographic location at which Halford Mackinder’s Heartland Theory and the Rimland Theory by Nicholas Spykman collide. Traditionally, the Balochistan region is considered in the localized perspective, but according to this study, it is regarded as a shatter-belt, which connects the land force of Eurasia to the sea-power of the Indian Ocean. The analysis of the strategic topography of the area reveals that Balochistan is a key energy and trade route, namely the construction of the Gwadar Port. The study utilizes the use of the focus on the Pivot Area brought forward by Mackinder to explain how the dominance of this transit zone can enable landlocked Central Asian states to avoid the traditional bottlenecks. At the same time, the paper relies on Spykman Rimland paradigm to emphasize the position of Balochistan in the inner crescent in which its accessibility to the sea poses a threat to the containment policies by world superpowers. The results indicate that the convergence of the two classical theories changes Balochistan into a peripheral region to a central Great Power competition region. This paper arrives at the conclusion that the area is no longer a border but a decisive contact point where the search after the continental depth is connected to the need of the naval accessibility which has a considerable impact on the 21st century geopolitics of South and Central Asia.